Changes in selected characteristics of river regime in Poland under climate warm-ing conditions - Wrzesiński, Dariusz (Acta Geographica Lodziensia, 2024)
The aim of this paper is to present the spatial and temporal differentiation of the stability and uncertainty of the river runoff regime in Poland in the years 1951–2020. Based on the stability coefficient and measures resulting from Shannon's information entropy theory, the degree of regularity and uncertainty in the annual cycle of maximum and minimum monthly runoff in the multi-annual period 1951–2020 was determined. The study revealed that changes in stability and uncertainty as well as the timing of the maximum and minimum runoff during the warming period after 1988 were spatially differentiated. The stability of the maximum runoff decreased in rivers in central Poland and rivers in the eastern part of the country and increased in most coastal and lake district rivers as well as the Sudeten tributaries of the middle Oder and the Carpathian tributaries of the Vistula up to the Dunajec River. The timing of the maximum runoff was both accelerated from spring to winter-spring, and delayed from winter-spring to spring and spring to spring-summer. The stability of the minimum runoff in many rivers (37% of profiles) increased significantly, but without a significant change in the date of its occurrence. The stability of the minimum runoff decreased, and the timing of its appearance was accelerated in the case of mountain rivers and the Odra and Vistula up to Dęblin.